THE UNITY OF MEANINGS IN THE VOCATIONAL HIGH SCHOOL ENGLISH TEXTBOOK (Universitas Negeri Semarang, 2014)
This study aims to describe the cohesion, coherence, thematic progression and the unity of meanings of the texts in the tenth grade of vocational high school textbook. There are twenty five texts in English textbook published by LP2IP as the data source. This study is a descriptive qualitative discourse analysis. The finding show that the high percentage of cohesive devices is reference and repetition, which means that the texts are cohesive enough. The use of reference and coherence contribute the unity of meanings grammatically and lexically. The high percentage of reiteration theme in the texts means that the texts use simple sentence. The use of simple sentence is because the readers are students of tenth grade vocational high school. There are five out of twenty five texts that have problem in thematic progression. 80% texts are unified, and 20 % are problematic text. The problems occur because of the overuse of reiteration theme and the unconnected idea of the clauses. As a material in teaching and learning, texts should be unified to make the students easy to understand.